2012
DOI: 10.1111/j.1741-2358.2012.00629.x
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans’s cell histiocytosis in old subjects: two rare case reports and review of the literature

Abstract: Langerhans's cell histiocytosis in old subjects: two rare case reports and review of the literature Background: Langerhans cell histiocytosis (LCH) is a proliferative disease of histiocyte-like cells that generally affects children; LCH onset is rare in adults; immunohistochemistry is essential to obtain the correct diagnosis, and treatment protocols are controversial. Objective: To describe two new cases of adult onset oral LCH. Case reports: Case 1: a 71-year-old woman, complaining of diffuse oral pain, pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 28 publications
(51 reference statements)
3
16
0
Order By: Relevance
“…The mucosal lesion may develop as gingival mass if lesion has broken out of the bone. [15] In the present case, similar features were present.…”
Section: Discussionsupporting
confidence: 82%
“…The mucosal lesion may develop as gingival mass if lesion has broken out of the bone. [15] In the present case, similar features were present.…”
Section: Discussionsupporting
confidence: 82%
“…LCH in elderly subjects is rare, and it has been presented mainly as case reports. 18,19 Although other studies have reported that males were more affected than females, [13][14][15] proportion of male and female patients was similar in our study.…”
Section: Discussionsupporting
confidence: 68%
“…Systemic involvement of certain organs affects negatively the prognosis. In fact, if high‐risk organs (liver, spleen, bone marrow, and lungs) are involved, mortality ranges reaches 30–50%, in comparison with a mortality risk of 10% when these organs are not affected …”
Section: Discussionmentioning
confidence: 99%
“…Localized disease is described as eosinophilic granuloma, while multisystem forms of LCH have eponymous descriptions such as Hand–Schüller–Christian disease, Letterer–Siwe disease, and systemic LCH …”
Section: Introductionmentioning
confidence: 99%